Development of Comic-Strip Digital Media with STEM Approach in Class XI Disaster Mitigation Materials - Indriani, Yuristya Dyah; Sahrina, Alfi; Utomo, Dwiyono Hari; Masruroh, Heni (Future Space: Studies in Geo-Education, 2025)
There is a significant need for digital media to support the learning of disaster mitigation materials, as existing learning tools are limited. Integrating these materials with a STEM approach enhances comprehensive understanding. Digital media, particularly in the form of comic strips, provides an accessible and engaging platform for students, especially as mobile devices such as smartphones—widely owned by students—can be used. This research and development aimed to maximize technology utilization in learning by creating a Digital Comic-strip learning tool for disaster mitigation in Class XI, incorporating the STEM approach. The ADDIE model, consisting of five stages—analysis, design, development, implementation, and evaluation—was employed in this study. The research was conducted at SMAN 1 Kepanjen, with a small-scale trial involving 10 students from Class XI IIS 4 and full implementation in a single class. Both qualitative and quantitative data were collected. The results demonstrate that the Digital Comic-strip media, which incorporates STEM principles, effectively supports disaster mitigation learning. The expert validation confirmed the media’s high feasibility, highlighting its effectiveness in meeting educational objectives and its potential to enhance student engagement in disaster mitigation topic.